St. John's Wort St. John's Wort (Hypericum perforatum) as an Alternative Treatment for Depression - Anggraeni, Arlian Puri (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2025)
Depression is one of the most common mental disorders worldwide that has a significant impact on the quality of life of individuals and society. Depression has recently become one of the mental health illnesses that many people in Indonesia experience, but Indonesian people do not yet have concerns about the treatment of depression, especially mild depression. Conventional depression treatments that already exist, such as selective serotonin reuptake inhibitor (SSRI) antidepressants, have been proven effective, but have side effects so that people are afraid to undergo treatment. St. John's Wort (Hypericum perforatum) is one of the alternative treatments for depression that is popular throughout the world, but in Indonesia there is no herbal medicine industry company that has developed this plant as a treatment for mild depression with herbs. This review aims to review the effectiveness and safety of St. John's Wort as a treatment for depression, as well as discuss its potential benefits and limitations. Based on a literature review, St. John's Wort has been shown to be effective in reducing symptoms of depression in patients with mild to moderate depression. However, of course, it still needs to be used with caution because of the potential for side effects and interactions with other drugs. Thus, St. John's Wort can be an alternative treatment for depression with new herbs in Indonesia that is effective, but it needs to be used under strict supervision.